2016
DOI: 10.1007/978-3-319-39745-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Change—North Sea

Abstract: This chapter discusses past and ongoing change in the following physical variables within the North Sea: temperature, salinity and stratification; currents and circulation; mean sea level; and extreme sea levels. Also considered are carbon dioxide; pH and nutrients; oxygen; suspended particulate matter and turbidity; coastal erosion, sedimentation and morphology; and sea ice. The distinctive character of the Wadden Sea is addressed, with a particular focus on nutrients and sediments. This chapter covers the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 289 publications
(347 reference statements)
2
13
0
Order By: Relevance
“…While it is well established that the North Sea has warmed substantially in recent decades (e.g. Huthnance et al 2016), with many documented impacts on fish species and the fisheries dependent on these (e.g. Simpson et al 2011;Heath et al 2012;Pinnegar et al 2016), to our knowledge, this is the first study to have systematically identified extreme temperature events and how these may have impacts on key fish and shellfish stocks.…”
Section: Discussionmentioning
confidence: 94%
“…While it is well established that the North Sea has warmed substantially in recent decades (e.g. Huthnance et al 2016), with many documented impacts on fish species and the fisheries dependent on these (e.g. Simpson et al 2011;Heath et al 2012;Pinnegar et al 2016), to our knowledge, this is the first study to have systematically identified extreme temperature events and how these may have impacts on key fish and shellfish stocks.…”
Section: Discussionmentioning
confidence: 94%
“…It is worth noting that B. ostreae exhibited high survival under the full range of pH and temperature conditions tested. Besides, the tested range of temperature and pH is far greater than the actual changes in the variables predicted in Huthnance et al (2016) for the end of this century, so it seems unlikely that the Bonamia parasite will be strongly negatively impacted by climate change in the near to medium term. However, specific research on the interactions between climate change effects and Bonamia is needed to test this hypothesis.…”
Section: Characteristics Of B Ostreae and Bonamiosis And The Relevanmentioning
confidence: 86%
“…General effects of climate change include higher temperature and (through dissolution of CO 2 ) lower pH (Huthnance et al, 2016). To our knowledge, there are no specific studies of the impact on the prevalence and/or the mortality caused by Bonamia infection to O. edulis populations under these climate change scenarios.…”
Section: Characteristics Of B Ostreae and Bonamiosis And The Relevanmentioning
confidence: 99%
See 1 more Smart Citation
“…Winter seawater temperatures in E England and S Norway (> 7°C: Mathis et al ) are higher than those currently experienced by adults in the German Bight (< 4°C), where populations of H. sanguineus persist over the winter (Geburzi et al ). Such difference in winter temperature is likely to result from coastal waters of E England and S Norway being influenced by the inflow of North Atlantic water, bringing water from the warm north–eastern limb of the Atlantic Meridional Overturning Circulation (Otto et al , Huthnance et al ). Another point is that models are based on records of surface temperature while larvae may occur deeper in the water column.…”
Section: Discussionmentioning
confidence: 99%